2021
DOI: 10.3389/fpubh.2021.660256
|View full text |Cite
|
Sign up to set email alerts
|

Community-Based Interventions as Opportunities to Increase HIV Self-Testing and Linkage to Care Among Men Who Have Sex With Men – Lessons From Ghana, West Africa

Abstract: MSM in Ghana encounter challenges in accessing HIV services and may experience barriers to HIV self-testing due to multiple forms of stigma present in health care settings. We worked with community-based organization partners to implement three interventions that successfully engaged and retained MSM which provides an opportunity for linkage to self-testing and medical care. These interventions were (1) Many Men Many Voices (3MV) a locally-led culturally grounded group-level HIV prevention program, (2) Auntie'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(59 citation statements)
references
References 27 publications
4
40
0
Order By: Relevance
“…In this paper, we describe the intervention and the adaptation process to serve as a guide for scholars and program implementers with interest in adapting interventions that will employ culturally relevant techniques and communication strategies to provide secured peer support targeted at improving HIV prevention and care among key populations in highly stigmatized environments. Our team created the currently adapted intervention to link people living with HIV with their peers, who can relate to their experiences living with HIV, and support them via effective information sharing, emotional connection, and linkage to nurses via a mobile platform [ 1 ].…”
Section: The Dennis Peer Support Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…In this paper, we describe the intervention and the adaptation process to serve as a guide for scholars and program implementers with interest in adapting interventions that will employ culturally relevant techniques and communication strategies to provide secured peer support targeted at improving HIV prevention and care among key populations in highly stigmatized environments. Our team created the currently adapted intervention to link people living with HIV with their peers, who can relate to their experiences living with HIV, and support them via effective information sharing, emotional connection, and linkage to nurses via a mobile platform [ 1 ].…”
Section: The Dennis Peer Support Modelmentioning
confidence: 99%
“…In Ghana, men who have sex with men (MSM) experience multilevel stigma due to intersecting marginalized identities (e.g., sexual orientation, gender identity, HIV status) that contribute to adverse health outcomes [ 1 , 2 ]. In Ghana, same-gender sexual behavior may be punishable by up to three years of imprisonment [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to conduct more active follow-up, obtaining contact information and unique personal identifiers (including biometrics) of clients is key to facilitate counseling text-messaging (along with specific locations of HIV clinics) and phone-based follow-up ( 10 ). In Ghana, a few strategies using community-based platforms have been piloted with success among the MSM population ( 36 ). These pilot interventions showed that virtual community-based platforms through mobile and digital technology could be used to link MSM to HIV care providers.…”
Section: Discussionmentioning
confidence: 99%
“…These pilot interventions showed that virtual community-based platforms through mobile and digital technology could be used to link MSM to HIV care providers. One intervention provided access to peers via an online app for peer support and referral to the providers (36). Toll-free telephone hotlines, online counseling, and automated text messaging may also be considered for counseling and facilitating linkage to care (8,10,19,(37)(38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%